(untitled) (INNOVATIVE ECONOMY, 2024)
Vatamanyuk-Zelinska U.Z., Kazakova O.O. EQUALIZATION OF LOCAL BUDGET DISPROPORTIONS THAT AROSE IN CONNECTION WITH FULL-SCALE WAR Purpose. The purpose of the article is to outline ways to resolve issues related to overcoming imbalances in the local budgets of the regions of Ukraine most affected by Russian aggression. Methodology of research. General scientific and empirical methods based on a systemic approach were used in the research process. The methods of statistical data processing and grouping were used to analyse disparities in local budgets of the most affected regions, as well as the method of system analysis. Findings. The article analyses the dynamics and structure of revenues and expenditures of local budgets of Ukraine under martial law. The negative impact of the full-scale war on the revenues and expenditures of local budgets was established, in particular, the identification of budget deficits, failure to ensure income growth of the Kherson, Donetsk, and Luhansk regions. The percentage value of the performance indicators of local budgets was established. Balance coefficients and volumes of interbudgetary transfers were determined. The following methods of equalizing disparities in the income and expenditure parts proposed by the authors to ensure the financial stability of local authorities and the balance of their budgets: reducing expenses, expanding external financing, using interbudgetary transfers. The importance of the additional subsidy aimed at equalizing disparities in territorial development and contributing to the stability of local budgets is indicated. Originality. The article provides a detailed analysis of the influence of martial law on the formation and implementation of the revenue and expenditure part of local budgets of Ukraine was carried out, taking into account statistical data and legislative changes. In addition, a number of methods of equalizing the disparities of local budgets are proposed, which can be used to ensure the stability and balance of the financial resources of the local government in the conditions of martial law. Practical value. The results of the research can be used to develop effective mechanisms for equalizing the disparities of the income and expenditure parts of local budgets in the conditions of martial law and ensuring their balance at the local level. Key words: local budgets, disparities, balancing, revenues, expenditures, interbudgetary transfers, additional subsidy.